Integrative Approach to Evaluation of Physical, Chemical and Biological Parameters: Analysis of Mujur River Water Quality - Supardiono, Supardiono; Rahayu, Rachmawati Noviana; Nurhidayatullah, Nurhidayatullah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This study uses an integrative approach to evaluate physical, chemical and biological parameters in the analysis of Mujur River water quality. This shows the complexity of interactions between various factors in determining river water quality. The purpose of this study was to understand the integrative impact of such factors on water quality. The research method involves collecting physical, chemical and biological data from the upstream, middle and downstream locations of the Mujur River. The results showed a complex pattern of interaction between physical, chemical and biological parameters that provided a deep understanding of river conditions. The conclusion of this study is the importance of an integrative approach in evaluating river water quality. In the future, it is necessary to implement more effective management measures to ensure the sustainability of the Mujur River and the surrounding ecosystem.